2013
DOI: 10.1039/c3cc45082a
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical studies and submicron ring formation of morpholino U-nucleoside monomers

Abstract: Synthesis, photophysical properties and submicron ring formation of functionalized uracil morpholino monomers have been reported. A series of characterization techniques indicated that the rings are formed by the inter-molecular hydrogen bonding of the uracil nucleus having a trityl-protected morpholino moiety. This is the smallest nucleoside unit known to date for submicron size ring formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Fast isomer Slow isomer ESI+ (m/z) NH 3 10.37 (13) CH 3 NH 2 9.97 (11) Et 2 NH 9.49 (15) 8.03 (17) 6.92 (19) 2.14 (21) 8.89 (23) 8.76 (25) 6.75 (28) NH 2 8.49 (30) 9.32 (24) 8.59 (26) 10.43 (14) 10.28 (12) 10.15 (16) 8.56 (18) 7.39 (20) 2.62 (22) 903. 64 We also note that because this chemistry is orthogonal to other methods of DNA modification such as copper activated click reactions 18 or palladium catalyzed Stille couplings 19 , it opens avenues for labelling DNA with multiple functional groups and fluorophores.…”
Section: Nhr'r''mentioning
confidence: 99%
See 1 more Smart Citation
“…Fast isomer Slow isomer ESI+ (m/z) NH 3 10.37 (13) CH 3 NH 2 9.97 (11) Et 2 NH 9.49 (15) 8.03 (17) 6.92 (19) 2.14 (21) 8.89 (23) 8.76 (25) 6.75 (28) NH 2 8.49 (30) 9.32 (24) 8.59 (26) 10.43 (14) 10.28 (12) 10.15 (16) 8.56 (18) 7.39 (20) 2.62 (22) 903. 64 We also note that because this chemistry is orthogonal to other methods of DNA modification such as copper activated click reactions 18 or palladium catalyzed Stille couplings 19 , it opens avenues for labelling DNA with multiple functional groups and fluorophores.…”
Section: Nhr'r''mentioning
confidence: 99%
“…Chemically modified oligodeoxynucleotides (ODNs) are used for applications in diagnostics, biomedical research, therapeutics, forensics, and material sciences. For therapeutic applications, the modifications are introduced to confer properties such as enhanced nuclease stability, improved pharmacokinetics, stronger and more selective binding to complementary DNA/RNA, and improved cellular uptake. On the other hand, the use of DNA-based sensors, nanomaterials, diagnostic tools, and catalysts requires the attachment of labels such as fluorophores, quenchers, metal complexes, and electron paramagnetic resonance (EPR) labels …”
Section: Introductionmentioning
confidence: 99%
“…9 Therapeutic development of PMOs is currently underway in ongoing clinical trials for treatment of Duchenne muscular dystrophy (DMD) and against the infection and spread of the hemorrhagic filovirus Marburg. 10 Recent research has also demonstrated that PMOs may prove useful for studies in the nanotechnology 11 and surface hybridization 12 fields.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Chemically modified oligodeoxynucleotides (ODNs) are used for applications in diagnostics, biomedical research, therapeutics, forensics, and material sciences. For therapeutic applications, the modifications are introduced to confer properties such as enhanced nuclease stability, improved pharmacokinetics, stronger and more selective binding to complementary DNA/RNA, and improved cellular uptake . To date a large number of ODNs have been tested for biological activity with encouraging results that have stimulated much activity in this area.…”
Section: Introductionmentioning
confidence: 99%